Ammonia borane destabilized by aluminium hydride: A mutual enhancement for hydrogen release. (12th January 2015) - Wan, Lei; Chen, Jie; Tan, Yingbin; Gu, Qinfen; Yu, Xuebin
Abstract: Destabilized by aluminum hydride, the dehydrogenation properties of ammonia borane (AB) can be improved significantly, including enhanced dehydrogenation kinetics, reduced induction period and suppressed formation of volatile byproducts. Furthermore, a lowered dehydrogenation temperature was also achieved for AlH3, indicating a mutual dehydrogenation enhancement for both AB and AlH3 in this mixture. The destabilized sample, 3AB/AlH3, can totally release more than 12 wt% of high-pure hydrogen (>99 wt%) without any detectable by-products below 250 °C. Mechanism investigations indicated that the mutual dehydrogenation enhancement in the mixture is attributed to the Coulombic attraction between the hydridic H δ− in AlH3 and the protonic H δ+ in the NH3 group of AB. Graphical abstract: A novel modification strategy that destabilize AB with AlH3 is employed to achieve a mutual enhancement for hydrogen release–> 12 wt. % pure H2 released below 250 ° C for the 3AB/AlH3 sample. Highlights: Aluminum hydride was applied to improve dehydrogenation of ammonia borane. A mutual dehydrogenation enhancement for both AB and AlH3 in the 3AB/AlH3 sample. Over 12 wt% of high-pure hydrogen (>99 wt%) can be released from 3AB/AlH3 below 250 °C.